Klasyfikacja rozumowań w świetle teorii pytań - Jedynak, Anna (Filozofia Nauki, 2003)
The aim of the paper is to show the value of the reasonings guided by questions based on uncertain assumptions. The notion of a properly asked question is being redefined to include questions based on uncertain assumptions. As a result, the classification of simple reasonings, originally set up by K. Ajdukiewicz, is presented as more detailed. Moreover, the paper sets up the classification of complex reasonings.